Cytotoxicity and bioactivity of calcium silicate cements combined with niobium oxide in different cell lines - Mestieri, Leticia Boldrin [UNESP]; Gomes-Cornélio, Ana Lívia [UNESP]; Rodrigues, Elisandra Márcia [UNESP]; Faria, Gisele [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mário [UNESP] (FapUNIFESP (SciELO), 2017)
The aim of this study was to evaluate the cytotoxicity and bioactivity of calcium silicate-based cements combined with niobium oxide (Nb2O5) micro and nanoparticles, comparing the response in different cell lines. This evaluation used four cell lines: two primary cultures (human dental pulp cells - hDPCs and human dental follicle cells - hDFCs) and two immortalized cultures (human osteoblast-like cells - Saos-2 and mouse periodontal ligament cells - mPDL). The tested materials were: White Portland Cement (PC), mineral trioxide aggregate (MTA), white Portland cement combined with microparticles (PC/Nb2O5μ) or nanoparticles (PC/Nb2O5n) of niobium oxide (Nb2O5). Cytotoxicity was evaluated by the methylthiazolyldiphenyl-tetrazolium bromide (MTT) and trypan blue exclusion assays and bioactivity by alkaline phosphatase (ALP) enzyme activity. Results were analyzed by ANOVA and Tukey test (α=0.05). PC/Nb2O5n presented similar or higher cell viability than PC/Nb2O5μ in all cell lines. Moreover, the materials presented similar or higher cell viability than MTA. Saos-2 exhibited high ALP activity, highlighting PC/Nb2O5μ material at 7 days of exposure. In conclusion, calcium silicate cements combined with micro and nanoparticles of Nb2O5 presented cytocompatibility and bioactivity, demonstrating the potential of Nb2O5 as an alternative radiopacifier agent for these cements. The different cell lines had similar response to cytotoxicity evaluation of calcium silicate cements. However, bioactivity was more accurately detected in human osteoblast-like cell line, Saos-2.
Keywords: Alkaline phosphatase; Cytotoxicity; Mineral trioxide aggregate; Nanoparticles; Niobium oxide